2017
DOI: 10.1002/smi.2740
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial safety climate, emotional exhaustion, and work injuries in healthcare workplaces

Abstract: Preventing work injuries requires a clear understanding of how they occur, how they are recorded, and the accuracy of injury surveillance. Our innovation was to examine how psychosocial safety climate (PSC) influences the development of reported and unreported physical and psychological workplace injuries beyond (physical) safety climate, via the erosion of psychological health (emotional exhaustion). Self-report data (T2, 2013) from 214 hospital employees (18 teams) were linked at the team level to the hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 56 publications
9
83
0
5
Order By: Relevance
“…Maslach, Schaufeli, and Leiter (2001) indicated that exhaustion is the major component of burnout and that "I'm exhausted" was also the first expression people used when experiencing burnout. Many researchers have also adopted the emotional exhaustion dimension to measure burnout (Fernández-Castro et al, 2017;Hülsheger, Alberts, Feinholdt, & Lang, 2013;Zadow, Dollard, Mclinton, Lawrence, & Tuckey, 2017).…”
Section: Authentic Leadership and Emotional Exhaustion Component Ofmentioning
confidence: 99%
“…Maslach, Schaufeli, and Leiter (2001) indicated that exhaustion is the major component of burnout and that "I'm exhausted" was also the first expression people used when experiencing burnout. Many researchers have also adopted the emotional exhaustion dimension to measure burnout (Fernández-Castro et al, 2017;Hülsheger, Alberts, Feinholdt, & Lang, 2013;Zadow, Dollard, Mclinton, Lawrence, & Tuckey, 2017).…”
Section: Authentic Leadership and Emotional Exhaustion Component Ofmentioning
confidence: 99%
“…While most of the previous studies on PSC have focused on the primary function of PSC, as direct effect or the mediating effect (Idris, Dollard, Coward, & Dormann, ; Idris et al ., ), our study adds to the PSC literature by exploring its secondary function (i.e., as a moderating effect) and the mechanism behind this. Third, with increased research attention on health care workplace safety, as PSC is related to workplace injuries (Zadow, Dollard, McLinton, Lawrence, & Tuckey, ), we have responded to the calls from researchers to examine the origins of workplace safety such as organizational climate and worker psychological health in health care settings. Finally, we tested our research framework in Malaysia, a developing Eastern country with rapidly increasing work pace and competitiveness due to global demands, given that research on the psychosocial risk factors in developing countries is still lacking (Kortum & Leka, ; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional exhaustion means a loss of enthusiasm for work . In our study, the frequency of high EE in the 31 to 40 age group was higher than in other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout is usually measured by the Maslach Burnout Inventory (MBI). EE is a feeling of energy deficiency and measures feelings of being emotionally overextended and exhausted by work; DP is defined as impersonal and even cynical attitudes toward patients or coworkers and measures an unfeeling and impersonal response toward recipients of one's service, care treatment, or instruction; PA refers to a decrease in self‐esteem or perceived performance and measures feelings of competence and successful achievement in work.…”
Section: Introductionmentioning
confidence: 99%